2021
DOI: 10.5296/ijld.v11i3.18946
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self – Efficacy and Readiness for Self – Directed Learning of Students at Vietnam University

Abstract: The research aims to investigate the readiness of self–directed learning, self–efficacy, and the relationship between them in students at the University of Social Science and Humanities Vietnam National University Ho Chi Minh City. The study was administrated with the self-efficacy scale developed by Schwarzer, R., & Jerusalem, M. (1993) and the readiness for self–directed learning scale developed by Fisher et al. (2001, 2010). The total number of students at the University of Social Sciences and Humanitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Most studies identified self-efficacy as one of the significant predictors or moderators for learning outcomes in a MOOC environment, such as academic success [31], completion rate [32], perceived effectiveness of MOOC [33], MOOC learners' learning persistence [34], and increased motivation level [35]. Some other studies investigated the sources of MOOC learners' self-efficacy [36]. Last, given the importance of self-efficacy in self-directed learning, other studies examine the extent to which specific pedagogical activities may improve MOOC learners' self-efficacy, such as co-design and delivery of MOOCs [37,38].…”
Section: Research Gaps and Research Questionsmentioning
confidence: 99%
“…Most studies identified self-efficacy as one of the significant predictors or moderators for learning outcomes in a MOOC environment, such as academic success [31], completion rate [32], perceived effectiveness of MOOC [33], MOOC learners' learning persistence [34], and increased motivation level [35]. Some other studies investigated the sources of MOOC learners' self-efficacy [36]. Last, given the importance of self-efficacy in self-directed learning, other studies examine the extent to which specific pedagogical activities may improve MOOC learners' self-efficacy, such as co-design and delivery of MOOCs [37,38].…”
Section: Research Gaps and Research Questionsmentioning
confidence: 99%
“…Research, including studies by Abdullah and Suan (2015), Khamkhong (2018), and others, indicates that Asian university students often lack critical reading skills and the higher order thinking necessary for tertiary education. While existing literature predominantly examines English language courses, contradictory findings emerge regarding the critical reading skills of Malaysian and Vietnamese students, with little focus on tertiary-level students in science or engineering (Azizi-Fini et al, 2015; Looi et al, 2022; Phan, 2023; Thuy, 2018). Critical reading, closely related to critical thinking (Paul and Elder, 2019), involves deep comprehension and a critical stance toward information that is pivotal in both personal and professional settings.…”
Section: Introductionmentioning
confidence: 99%